Consumer protection in relation to direct marketing - targeted advertising under EU e-commerce legislation - Šampiņa, Ilze (Riga Graduate School of Law, 2018)
The thesis analyses issues on consumer protection in the context of direct marketing – targeted advertising under EU e-commerce legislation. The research provides an in-depth examination of aspects concerning the linkage between consumer protection, on the one hand, and traders’ interests in developing business and providing information about their products and services to consumers, on the other hand.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Consumer protection; E-commerce